Report of Incidental Vulvar Malignant Melanoma Upon Dermatologic Evaluation for Vaginal Cyst - Vrusha K. Shah; Alaina J. James; Sarah E. Taylor; Diwakar Davar; Noel Provost (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Vulvar malignant melanoma is a rare, often aggressive and recurring disease with a poorly understood prognosis. Here, we describe a patient with a longstanding vaginal cyst who was diagnosed with vulvar malignant melanoma upon a dermatologic evaluation. THE CASE: Our patient, a 53-year-old female, with a family history of a father with malignant melanoma presented for evaluation of a vaginal cyst present for over 20 years on her right labia that had become painful and began draining over the past year. She was seen twice at urgent care and was treated with oral antibiotics (unspecified) and referred to dermatology. A comprehensive dermatologic evaluation of the epidermal inclusion cyst in the right labia majora incidentally revealed a neoplasm of uncertain behavior in the right labia minora suspected for vulvar malignant melanoma (Figure 1). Shave biopsy of her right labia minora revealed a Stage 1B malignant melanoma, superficial spreading type, with a 1.1 mm depth of invasion (Breslow thickness) and 11 per 1mm2 mitotic count. Right partial radical vulvectomy and bilateral inguinal sentinel lymph node biopsies were performed. Pathology showed malignant melanoma with negative margins and negative nodes. Treatment and excision for her vaginal cyst was not initiated as her symptoms were not bothersome at the time of visit.  She presented with a post-operative infection after 2 weeks which was suggestive of bilateral inguinal vulval acute cellulitis with no definitive abscess upon computed tomography (CT) scan. She was initially treated with vancomycin with additional piperacillin/tazobactam for a total of three days. Trimethoprim/sulfamethoxazole was later initiated for 14 days. Medical oncology referral for evaluation of metastasis revealed normal positron emission tomography-computed tomography scan. Notably, the patient had extensive confluent/atypical lentiginous basal melanocytic hyperplasia at the periphery which could not be distinguished from melanoma in situ. Upon tumor board consultation, scouting biopsies of her left labia majora were performed. Pathology showed melanocytic hyperplasia instead of residual malignant melanoma at the periphery. The patient now follows up every few months with dermatology and medical oncology. CONCLUSION: Given the often fast, aggressive spread of vulvar malignant melanoma, timely dermatologic evaluations are necessary. Among those at higher risk due to a personal or family history of malignant melanoma, regular total body skin cancer screenings are indicated. Further, the sensitive and typically sun-protected location of a vulvar malignant melanoma might preclude a dermatologic evaluation in this area and highlights the need for more comprehensive vaginal screenings and better communication between dermatologic and gynecologic medical care teams.